Assessment of 2012 EULAR/ACR new classification criteria for polymyalgia rheumatica in Japanese patients diagnosed using Bird's criteria. (6th March 2017) - Matsui, Kiyoshi; Maruoka, Momo; Yoshikawa, Takahiro; Hashimoto, Naoaki; Nogami, Mika; Sekiguchi, Masahiro; Azuma, Naoto; Kitano, Masayasu; Tsunoda, Shinichiro; Sano, Hajime
Abstract: Aim: The 2012 European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) classification criteria for polymyalgia rheumatica (PMR) were published in 2012. The present study aimed to assess the 2012 EULAR/ACR classification criteria for PMR in Japanese patients diagnosed with PMR using Bird's criteria. Methods: The study included 75 patients diagnosed using Bird's criteria. The patients were divided into fulfilled and not‐fulfilled groups according to whether they met the 2012 EULAR/ACR classification criteria for PMR. The factors in the new criteria were morning stiffness duration > 45 min, hip pain or limited range of motion, absence of rheumatoid factor or anti‐citrullinated protein antibody, and absence of other joint involvement. Results: Thirty‐two of the patients diagnosed with PMR using Bird's criteria met the new EULAR/ACR classification criteria, while the remaining 43 patients did not meet the new criteria. Among the factors, only morning stiffness duration > 45 min was an independent predictive factor. Conclusions: A morning stiffness duration > 45 min is the only independent predictive factor for differentiating patients diagnosed according to the new 2012 EULAR/ACR classification criteria for PMR.